Camouflaging Structural Diversity: Co‐crystallization of Two Different Nanoparticles Having Different Cores But the Same Shell. Issue 1 (25th November 2018) - Bodiuzzaman, Mohammad; Ghosh, Atanu; Sugi, Korath Shivan; Nag, Abhijit; Khatun, Esma; Varghese, Babu; Paramasivam, Ganesan; Antharjanam, Sudhadevi; Natarajan, Ganapati; Pradeep, Thalappil
Abstract: Two ligand‐protected nanoscale silver moieties, [Ag46 (SPhMe2 )24 (PPh3 )8 ](NO3 )2 and [Ag40 (SPhMe2 )24 (PPh3 )8 ](NO3 )2 (abbreviated as Ag46 and Ag40, respectively) with almost the same shell but different cores were synthesized simultaneously. As their external structures are identical, the clusters were not distinguishable and become co‐crystallized. The occupancy of each cluster was 50 %. The outer shell of both is composed of Ag32 S24 P8, which is reminiscent of fullerenes, and it encapsulates a well‐studied core, Ag14 and a completely new core, Ag8, which correspond to a face‐centered cube and a simple cube, respectively, resulting in the Ag46 and Ag40 clusters. The presence of two entities (Ag40 and Ag46 clusters) in a single crystal and their molecular formulae were confirmed by detailed electrospray ionization mass spectrometry. The optical spectrum of the mixture showed unique features which were in good agreement with the results from time‐dependent density functional theory (TD‐DFT). Abstract : Silver lining : Two ligand‐protected silver clusters, Ag46 and Ag40, with identical shells but different cores have been crystallized together. These clusters are the first examples of a new class of cluster solids.